Konsep Desain Healing Garden bagi Pasien Penyakit Jantung di Rumah Sakit Angkatan Darat Udayana Denpasar, Bali - Safitri, Nia; Krisnandika, Anak Agung Keswari; Dharmadiatmika, I Made Agus (Jurnal Arsitektur Lansekap, 2024)
Design of the Hospital Garden as a Healing Garden in Udayana Hospital for Heart Disease Patient. Heart disease is a disease with the highest risk of death in Indonesia. Healing heart disease can be done medically and can be done in an outdoor room with a healing garden which has cardiac therapy facilities in it to accelerate the healing process for patients and reduce patient stressors. So that environmental factors have an important role in the patient's healing process, but in reality the importance of the garden as a place of healing is ignored. In fact, a good garden design arrangement will help heal patients physically and non-physically. The purpose of this research is to produce a garden design concept that can support the healing of heart disease patients at Udayana Hospital. The concept applied to the hospital garden is the design concept of the healing garden Biomimicry. The research method used is a survey method with data collection techniques through observation, interviews, and literature study. The stages of the research carried out include inventory, analysis, synthesis, and design concept planning. The design concept is designed based on the needs of heart disease patients in their recovery period by paying attention to softscape and hardscape. The design concept of Biomimicry contains the philosophy of freedom, this is related to the space for physical movement, with freedom in physical movement, the healing process of heart disease patients will be faster physically and psychologically.